The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s12094-016-1539-4
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term oncologic outcome of a novel approach for locally advanced colon cancer with neoadjuvant chemotherapy and surgery

Abstract: Preoperative chemotherapy in LACC patients is safe and able to induce major tumor regression. Survival times are encouraging, and further research seems warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 25 publications
3
52
1
4
Order By: Relevance
“…Although neoadjuvant chemotherapy is not routinely administered in locally advanced colorectal cancer patients, several authors have demonstrated benefits with a neoadjuvant chemotherapy-alone approach [25,26]. Studies have shown that neoadjuvant chemotherapy with CAPOX or FOLFOX is effective and safe in patients with locally advanced colon cancers [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although neoadjuvant chemotherapy is not routinely administered in locally advanced colorectal cancer patients, several authors have demonstrated benefits with a neoadjuvant chemotherapy-alone approach [25,26]. Studies have shown that neoadjuvant chemotherapy with CAPOX or FOLFOX is effective and safe in patients with locally advanced colon cancers [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although neoadjuvant chemotherapy is not routinely administered in locally advanced colorectal cancer patients, several authors have demonstrated benefits with a neoadjuvant chemotherapy-alone approach. 25,26 Studies have shown that neoadjuvant chemotherapy with CAPOX or FOLFOX is effective and safe in patients with locally advanced colon cancers. 25,26 All patients in our study completed neoadjuvant chemotherapy without experiencing any major toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Studies have shown that neoadjuvant chemotherapy with CAPOX or FOLFOX is effective and safe in patients with locally advanced colon cancers. 25,26 All patients in our study completed neoadjuvant chemotherapy without experiencing any major toxicities. Although no patient achieved complete pathologic response in our study, tumor reduction was achieved in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although neoadjuvant chemotherapy is not routinely administered in locally advanced colorectal cancer patients, several authors have demonstrated benefits with a neoadjuvant chemotherapy-alone approach. 20,[25][26][27] A single-center phase II study conducted at Memorial Sloan-Kettering Cancer Center evaluated neoadjuvant chemotherapy with six cycles of FOLFOX plus bevacizumab in locally advanced rectal cancer patients and showed that neoadjuvant chemotherapy was relatively safe and capable of inducing major tumor regression. 25 Four cycles of neoadjuvant mFOLFOX6 chemotherapyalone approach has also shown promising efficacy for locally advanced rectal cancer in the FOWARC study.…”
Section: Discussionmentioning
confidence: 99%
“…26 Other studies have shown that neoadjuvant chemotherapy with CAPOX or FOLFOX is effective and safe in patients with locally advanced colon cancers. 20,27 All patients in our study completed neoadjuvant chemotherapy without experiencing any major toxicities. Although no patient achieved complete pathologic response in our study, tumor reduction was achieved in all patients.…”
Section: Discussionmentioning
confidence: 99%